Prevalence, Virulence Traits and Antimicrobial Resistance Pattern of Staphylococcus aureus Isolated from Chicken - Doiphode, Amruta; Waskar, Vikas; Kolhe, Rahul; Kadam, Bapurao; Mhase, Prashant (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Staphylococcus aureus isolated from chicken samples of retail market of Shirwal city exhibited 36% (18/50) prevalence, confirmed biochemically as well as by polymerase chain reaction by employing 16s-rDNA and species-specific sau genes. None of the isolates were found to possess virulence genes, viz., sea, seb, sec and sed. Antimicrobial resistance pattern revealed that 100% isolates were resistant to 16 among 24 antibiotics, while 5 antibiotics showed more than 70% resistance, except for tobramycin (44.44%) and gentamicin, streptomycin (38.89% each). All isolates were multidrug resistant (MDR). Screening for the presence of antimicrobial resistance genes revealed the presence of aacA-D, ermA, tetK and tetM genes. None of the isolates carried mecA, mrsA, mrsB, vanA, vanB and ermC genes, although phenotypic resistance was noted.